2018
DOI: 10.1186/s12645-017-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

C60 fullerene and its nanocomplexes with anticancer drugs modulate circulating phagocyte functions and dramatically increase ROS generation in transformed monocytes

Abstract: BackgroundC60 fullerene-based nanoformulations are proposed to have a direct toxic effect on tumor cells. Previous investigations demonstrated that C60 fullerene used alone or being conjugated with chemotherapeutic agents possesses a potent anticancer activity. The main aim of this study was to investigate the effect of C60 fullerene and its nanocomplexes with anticancer drugs on human phagocyte metabolic profile in vitro.MethodsAnalysis of the metabolic profile of phagocytes exposed to C60 fullerene in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 82 publications
(107 reference statements)
2
25
0
Order By: Relevance
“…The estimation of C 60 FAS impact on Drosophila melanogaster at DNA, tissue, and organism levels showed that C 60 at the concentration 40 μg/mL does not affect the reproductive system and embryogenesis [50]. Recently, a low toxicity of C 60 FAS towards human embryonic kidney (HEK293) cells and mice (IC 50 383.4 μg/mL, LD 50 721 mg/kg) [51] and the selective strong toxic effect of C 60 FAS against tumor cells (rat and human glioma cells) and transformed human phagocytes [52] were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of C 60 FAS impact on Drosophila melanogaster at DNA, tissue, and organism levels showed that C 60 at the concentration 40 μg/mL does not affect the reproductive system and embryogenesis [50]. Recently, a low toxicity of C 60 FAS towards human embryonic kidney (HEK293) cells and mice (IC 50 383.4 μg/mL, LD 50 721 mg/kg) [51] and the selective strong toxic effect of C 60 FAS against tumor cells (rat and human glioma cells) and transformed human phagocytes [52] were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a sharp increase in ROS production after treatment with all the studied NP preparations and an eightfold increase caused by C60 fullerene NPs alone. It was therefore concluded that these particles are strong inducers of intracellular ROS generation and can possibly counteract the pro-oxidant effects of anticancer drugs like cisplatin [102].…”
Section: Leukocyte Function In Hemostasis and The Mechanisms Involmentioning
confidence: 99%
“…The degree of NP cellular uptake directly influences the cytotoxicity of the NP and must therefore be carefully considered during NP synthesis and design [78]. Furthermore, Pujari-Palmer et al found that NP geometry can have a pertinent influence on leukocyte functioning where fiber-shaped HAP-NPs inducing the greatest amount of ROS generation, caspase 3/7 activation and acute in vivo inflammation compared to other geometries such as rods, dots and sheets [102].…”
Section: The Influence Of Surface Chemistry On Nanoparticle Hemocomentioning
confidence: 99%
“…A study involving anti-cancer drug conjugated to C 60 fullerene showed C 60 to trigger phagocyte activity. In addition, fullerenes with anticancer drugs promotes ROS production by phagocytes, a promising strategy for treatment of cancer ( Skivka et al, 2018 ).…”
Section: Nanotechnology For Cancer Diagnosismentioning
confidence: 99%